Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.218
|View full text |Cite
|
Sign up to set email alerts
|

Surface Complexation Modeling for the Stabilization of an Industrial Sludge by Alternate Materials

Abstract: The main aim of this paper is to model the behavior of a mixture of 30% fly ash, 60% black cotton soil, 30% heavy metal laced industrial sludge and 15% cement for sorption of chromium and copper at different pH values. It was found that the mixture of 30% fly ash, 60% soil, 30% sludge and 15% cement was the ideal combination found from extensive leaching experiments, for heavy metals such as Cr +6 and Cu 2+ . Owing to practical difficulties in carrying out leaching tests over wide range of pH values, Visual mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…This slurry was agitated with a mechanical shaker at room temperature (25±2°C) for 2 h until the pH was stabilized. The pH of the slurry was adjusted to the desired value in the range of 2 to 10 with 0.1M HNO3 and NaOH [27][28][29].…”
Section: Batch Equilibrium Test Proceduresmentioning
confidence: 99%
“…This slurry was agitated with a mechanical shaker at room temperature (25±2°C) for 2 h until the pH was stabilized. The pH of the slurry was adjusted to the desired value in the range of 2 to 10 with 0.1M HNO3 and NaOH [27][28][29].…”
Section: Batch Equilibrium Test Proceduresmentioning
confidence: 99%
“…This increased the efficacy of NCS as a stabilizing material for long-term attenuation requirements of the industry. Further, to validate the use of NCS as a soil amendment, many more leaching tests have been performed under various conditions [17,18,21]. It was found that because of the organic nature of BCS and being an expansive soil with low strength parameters, it was decided to continue further tests only with red soil.…”
Section: Results and Discussion Leaching Studiesmentioning
confidence: 99%
“…Re-adsorption usually happens under, 1) the presence of competitive ions; 2) the presence of extra precipitates induced by change of ambient geochemistry (e.g. pH); and 3) the presence of complexation surface (Moghal et al, 2014;Qiu et al, 2018;Wang et al, 2009). As seawater were extremely abundant surrounding IBA in all designated experiments, the competitive ions (born from IBA) would be greatly diluted (Yang et al, 2016) while seawater significantly buffers the changes of environmental chemistry in the solution induced from IBA (Cyronak et al, 2018;Fajar et al, 2015;Hain et al, 2015).…”
Section: Heavy Metal Re-adsorption Potentialmentioning
confidence: 99%